ANALISIS PENGARUH FASILITAS KREDIT, SUKU BUNGA, PENDAPATAN, JAMINAN KREDIT DAN JANGKA WAKTU TERHADAP KELANCARAN PEMBERIAN KREDIT PADA BPR WELERI MAKMUR SURAKARTA - Dewi Saptantinah Puji Astuti, Shanen Tahapary, Fadjar Harimurti & (Universitas Slamet Riyadi, 2017)
The purpose of this study is to analyze the effect of credit facilities on thesmoothness of lending, Analyzing the effect of interest rates on the smooth lending,Analyzing the effect of income on the smooth lending, Analyzing the effect of creditguarantees to the smooth lending, Analyzing the influence of credit period to thesmooth credit payments . Are all variables compatible with SPI. The object of thisresearch is BPR Waleri Makmur Surakarta. This study uses questionnaires given toemployees of BPR Waleri Makmur Surakarta on credit. Data analysis techniques usedescriptive data analysis. Based on the results of research on BPR Waleri MakmurSurakarta can be concluded that: The smoothness of credit provision in BPR WaleriMakmur Surakarta has been in accordance with the SPI. This is supported by thequestionnaire based on the assessment criteria, for all variable of credit facility76,16%, interest rate 77,00%, income 91,83%, credit guarantee 76,92%, creditperiod 76,46% and smoothness of giving Credit 88,88%. Thus the internal control isvery effective and the influential SPI element in this case is the organizationalstructure that separates the functional responsibilities explicitly, the authority systemand the procedure of recording and healthy practices in performing the duty towardsthe smooth lending of BPR Waleri Makmur Surakarta.Keywords: Credit facility, interest rate, income, credit guarantee, credit terms, creditpayment